Analisis Sistem E-Commerce pada Shopee untuk meningkatkan daya saing menggunakan metode S.W.O.T. - Candra Gudiato; Eko Sediyono; Irwan Sembiring (Journal of Information Technology, 2022)
The development of information technology has shifted the human paradigm in doing shopping from the traditional way that requires sellers and buyers to meet directly to electronic commerce (e-commerce) which is completely online. Shopee as one of the players in the e-commerce business has transformed into one of the big marketplaces, both in Indonesia and in the world. As an e-commerce company that has a worldwide reputation, Shopee is not the only player in the E-commerce business. To be able to survive in the midst of tight digital competition, of course Shopee is expected to always innovate to maintain service quality and increase competitiveness against its competitors. Therefore, an analysis will be carried out using S.W.O.T. to find out the strengths, weaknesses, opportunities, and threats that can occur to Shopee e-commerce. Based on the results of the analysis carried out, it was found that the strength of Shopee lies in its reputation, its weakness is that it is not e-commerce from Indonesia, the opportunity is a marketplace business that is not bound by space and time, and the threat is that there are many competitors for a similar business model. From these results, to reduce weaknesses and threats, as well as increase the strengths and opportunities that Shopee has, it can be done by implementing the S-O, W-O, S-T, and W-T strategies.